Sanksi Pidana Bagi Pengemudi Angkutan Umum Terhadap Kelalaian Yang Menyebabkan Kecelakaan - Gede Kristya Yuan Prayoga; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2025)
Several issues affecting road traffic safety are traffic accidents. The high number of accidents in Indonesia is one of the consequences of the low awareness of road users and transportation service providers regarding compliance with traffic regulations and road safety. Two legal questions arise: (1) What regulations apply to public transport drivers regarding negligence that causes accidents? (2) What are the penalties for public vehicle drivers who are negligent and cause traffic accidents? This study uses a normative legal research method. Regulations on public transportation drivers related to training. Training will be conducted more frequently on the highways or while public transportation is in motion, so that drivers better understand field conditions. Criminal sanctions imposed on public transportation drivers for their negligence are regulated in CHAPTER XX which governs the criminal provisions of Law of the Republic of Indonesia Number 22 of 2009 concerning Traffic and Road Transportation. However, many drivers still ignore this, leading to accidents. Therefore, training and education for public transportation drivers, as well as adjustments to the Investigators of Civil Service (PPNS) are needed to apply the law correctly.